Testing the blast-wave AGN feedback scenario in MCG-03-58-007. Issue 2 (13th August 2019) - Sirressi, M; Cicone, C; Severgnini, P; Braito, V; Dotti, M; Della Ceca, R; Reeves, J N; Matzeu, G A; Vignali, C; Ballo, L
Abstract: We report the first Atacama large millimeter/submillimeter array observations of MCG-03-58-007, a local ( z = 0.03236 ± 0.00002, this work) AGN (L_ AGN 10^45 erg s^-1 ), hosting a powerful X-ray ultrafast ( v = 0.1 c ) outflow (UFO). The CO(1-0) line emission is observed across ∼18 kpc scales with a resolution of 1 kpc . About 78 per cent of the CO(1-0) luminosity traces a galaxy-size rotating disc. However, after subtracting the emission due to such rotating disc, we detect with a S/N = 20 a residual emission in the central ∼4 kpc. Such residuals may trace a low velocity ( v LOS = 170 km s −1 ) outflow. We compare the momentum rate (P ) and kinetic power (E ) of such putative molecular outflow with that of the X-ray UFO and find P_ mol/P_ UFO0.4 and E_ mol/E_ UFO4× 10^-3 . This result is at odds with the energy-conserving scenario suggested by the large momentum boosts measured in some other molecular outflows. An alternative interpretation of the residual CO emission would be a compact rotating structure, distinct from the main disc, which would be a factor of ∼10–100 more extended and massive than typical circumnuclear discs revealed in Seyferts. In conclusion, in both scenarios, our results rule out the hypothesis of a momentum-boosted molecular outflow in this AGN, despite the presence of a powerful X-ray UFO.